From Dynamic Expression Patterns to Boundary Formation in the Presomitic Mesoderm - Tiedemann, Hendrik B.; Schneltzer, Elida; Zeiser, Stefan; Hoesel, Bastian; Beckers, Johannes; Przemeck, Gerhard K. H.; de Angelis, Martin Hrabě (PLOS Computational Biology, 2012)
Author Summary Somitogenesis is a process in embryonic development establishing the segmentation of the vertebrate body by the periodic separation of small balls of epithelialized cells called somites from a growing mesenchymal tissue, the presomitic mesoderm (PSM). The basic mechanisms are often discussed in terms of the clock-and-wave-front model, which was proposed already in 1976. Candidate genes for this model were found only in the last fifteen years with the cyclically expressed Hairy/Hes genes functioning as the clock and posteriorly expressed Fgf, Tbx6, and Wnt genes establishing the gradient(s). In addition, the Delta/Notch signal transduction pathway seems to be important for boundary formation between forming somites and the remaining PSM by inducing Mesp2 expression just behind a future somitic boundary. Although many in silico models describing partial aspects of somitogenesis already exist, there are still conflicts regarding the mechanisms of the somitogenesis clock. Furthermore, a simulation that fully integrates clock and gradient was only recently published for chicken. Here, we propose a cell- and gene-based computer model for mammalian somitogenesis, simulating a gene regulatory network combining clock (Hes1/7) and gradient (Tbx6, Fgf8, Wnt3a) with Delta/Notch signaling resulting in dynamic gene expression patterns as observed in vivo finally leading to boundary formation.